A novel screening system for secretion of heterologous proteins in Bacillus subtilis - Trip, Hein (Blackwell Publishing Ltd, 2011)
High‐level production of secretory proteins in Bacillus subtilis leads to a stress response involving the two‐component system CssRS and its target genes htrA and htrB. Here, we used this sensing system in a reporter strain in which gfp is under control of P(htrA), the secretion stress responsive promoter of htrA. Overexpression of heterologous secretory proteins in this strain results in green fluorescent cells, which can be separated from non‐secreting, low fluorescent cells using a fluorescence‐activated cell sorter (FACS). Using this principle, genomic libraries of uncharacterized prokaryotic organisms, expressed in the reporter strain, can be screened for genes encoding secretory proteins.